OLDP Assistance of Yayasan Cahaya Amal Soleh : Finance for Non-Finance using SiApik - Sri Wahyuningsih; Yulianawati Yulianawati; Wahyumi Ekawanti (Pusat Riset dan Inovasi Nasional, 2025)
Cahaya Amal Soleh Foundation is a social institution that focuses on community service through various institutional programs engaged in social, education, and community empowerment. However, a number of operational staff who do not have a financial background have difficulty in understanding and managing financial reports effectively. This study aims to assist staff through the On-the-Job Learning and Development Program (OLDP) themed Finance for Non-Finance with the SIAPIK (Islamic Boarding School and Social Charity Accounting Information System) application approach. The method used is a qualitative approach with a participatory model, involving direct training, transaction recording simulations, and evaluation of participant understanding. The results of the assistance showed a significant increase in staff understanding of basic accounting principles, transaction recording, and SIAPIK-based financial reporting. These findings indicate that a practical approach through an application based on the foundation's needs can improve the financial capacity of non-accounting staff. The implications of this activity reinforce the importance of digitizing the financial system of social organizations and the need for ongoing training for human resources so that accountable and transparent financial governance can be realized sustainably. In addition, the results of this program highlight that the integration of technology and participatory training can overcome barriers in financial literacy among non-finance staff. The SIAPIK application provides an accessible interface and structured modules that are easy to understand, thereby reducing the complexity usually associated with financial management. Staff who previously felt unconfident in processing financial transactions gradually gained competence and independence in applying accounting procedures. The training also fostered collaborative learning, where participants supported each other in solving case simulations, enhancing not only technical knowledge but also teamwork and problem-solving skills. Furthermore, the foundation’s management expressed that the program positively contributed to institutional performance by ensuring more reliable and transparent financial reporting.